From ICV 1.0 to ICV 2.0: real-time digital twin city construction for the coordinated development of ICV and smart city - Siyang LIU; Yunfei ZHANG (Dianxin kexue)
Based on the development status and industry challenges of intelligent connected vehicles (ICV), the concepts and development strategies of ICV 1.0 and ICV 2.0 were proposed.Pan-V2X which aimed to achieve the breakthrough of ICV 1.0 and the vehicle-city coordination platform which was the core platform of ICV 2.0 were introduced.The vision of ICV 2.0 was to build transport real-time digital twin based on ICV and real-time digital twin city for coordinated development of ICV and smart city.The construction methods and innovative practices of real-time digital twin city for coordinated development of ICV and smart city were finally introduced.